Increasing female authorship of foot and ankle academic literature over 24 years. Issue 3 (14th September 2018) - Sing, David; Vora, Molly; Kuripla, Casey; Ouyang, David
Category: Other Introduction/Purpose: Under-representation of women in surgery is commonly attributed to lacking mentorship and exposure in medical school, societal perceptions regarding career priorities, and concerns of "fitting in" in a work culture predominantly comprised of men. Furthermore, this disparity is also reflected in research productivity across academic medicine with male faculty being more likely to publish research compared to female colleagues. In this study we aim to describe the representation and longevity of female investigators among the authors of three foot and ankle research journals from 1993 to 2017. Methods: In this retrospective bibliometric analysis, authors of original research from three prominent foot and ankle research journals (Foot and Ankle International, The Journal of Foot and Ankle Surgery, Foot and Ankle Clinics) were extracted from PubMed. For authors with a complete first name listed, gender was determined by matching first name using an online database containing 216, 286 distinct names across 79 countries and 89 languages. Proportion of female first, middle, and senior authors were determined over time, as well as total publication count per author. A sub-analysis of authors first publishing between 2007-2012 was followed for 5 years to identify how often authors continued to publish after first publication. Student t-test, chi-square analysis, and Cochran-Armitage trend tests were used to determine significance between groups. Results: From 1993 to 2017, 8, 132 original articles were published in three foot and ankle research journals. A total of 6, 597 (81.1%) had first names listed, identifying 25, 329 total authors, of which 22, 961 (90.7%) were successfully matched to a gender. 9, 273 unique authors were identified (female: 19.2%). Female representation increased for first and senior authors from 6.5% and 5.9% (1993-1997) to 16.9% and 13.1% (2013-2017, p<0.001). Compared with male authors, female authors published fewer articles (mean: 1.7 vs 2.4, p<0.001). Of 2, 691 authors who first published during 2006 to 2011, 369 authors (13.0%; female: 8.1% vs male 15.0%, p<0.001) continued to publish 5 years after their first publication. Female authors were more likely to only publish one article (75.6% vs 69.4%, p=0.016). Conclusion: Female representation in academic foot and ankle research has increased over two-fold over the past 2 decades. Despite these advances, compared to male authors, female authors are less likely to continue publishing 5 years after initial publication, and on average publish fewer articles. Although women are increasingly supported in the surgical workforce, our findings suggest that disparities in academic productivity exist in foot and ankle surgery. Further analysis of barriers to research amongst women may result in more equitable academic advancement and promotion for female foot and ankle surgeons.